Ochotnicza straż pożarna jako stowarzyszenie - Kocowski, Tadeusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Volunteer fire brigades have a long history of operation. They operated as voluntary entities with the legal form of the association. Nowadays, acting as an association, they are also fire protection units. It places these units in a specific position.
Keywords: ochotnicza straż pożarna; stowarzyszenia; jednostka ochrony przeciwpożarowej; stowarzyszenie zwyczajne